2000
DOI: 10.1042/0264-6021:3460053
|View full text |Cite
|
Sign up to set email alerts
|

A pyruvate‒proton symport and an H+-ATPase regulate the intracellular pH of Trypanosoma brucei at different stages of its life cycle

Abstract: Regulation of intracellular pH (pH(i)) and H(+) efflux were investigated in Trypanosoma brucei bloodstream and procyclic trypomastigotes using the fluorescent dyes 2', 7'-bis-(2-carboxyethyl)-5(6)-carboxyfluorescein (BCECF) acetoxymethyl ester and free BCECF respectively. pH(i) in bloodstream and procyclic trypomastigotes was 7.47+/-0.06 and 7. 53+/-0.07 respectively. Differences in the mechanisms for the regulation of pH(i) were noted between bloodstream and procyclic forms. Procyclic trypomastigotes maintain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
39
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 31 publications
7
39
0
Order By: Relevance
“…Therefore, we analyzed the steady-state pH i of these mutants under different external pH (pH e ). In normal cells, the pH i remained close to 7.1 in the pH e ranges from 6.5 to 8 as reported previously (30,44). However, while the pH i of the induced mutant cells was maintained at acidic pH e , it increased almost 0.2 pH unit at basic pH e (Fig.…”
Section: Ca 2ϩ and Ph I Homeostasis In The Induced Pfivp1mentioning
confidence: 49%
See 1 more Smart Citation
“…Therefore, we analyzed the steady-state pH i of these mutants under different external pH (pH e ). In normal cells, the pH i remained close to 7.1 in the pH e ranges from 6.5 to 8 as reported previously (30,44). However, while the pH i of the induced mutant cells was maintained at acidic pH e , it increased almost 0.2 pH unit at basic pH e (Fig.…”
Section: Ca 2ϩ and Ph I Homeostasis In The Induced Pfivp1mentioning
confidence: 49%
“…To further investigate the role of the V-H ϩ -PPase in pH i regulation, procyclic trypomastigotes were acidified to a pH of ϳ6.0 using the NH 4 Cl prepulse technique (44). Fig.…”
Section: Ca 2ϩ and Ph I Homeostasis In The Induced Pfivp1mentioning
confidence: 99%
“…In other protozoans, such as Trypanosoma brucei, the inhibitory effects of 3-BrPA on parasite motility and the efflux of pyruvate resulted in parasite death due to a blockade of the enzyme glyceraldehyde-3-phosphate dehydrogenase (GAPDH) (19,20). It has been reported that this enzyme plays a significant role in the glycolytic flux of protozoa, such as Leishmania mexicana, Plasmodium falciparum, and T. brucei (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…In protozoa such as Trypanosoma brucei, 3-BrPA has inhibitory effects on (i) the motility of the parasite at 13.4 mM and (ii) the efflux of pyruvate at 5.6 mM due to blockage of GAPDH, leading the reduced parasite viability (19,20). These data prompted us to study the activity of 3-BrPA on the intracellular development of T. gondii in LCC-MK2 cells.…”
mentioning
confidence: 99%
“…The presence of pyruvate transporters in the plasma membrane of T. brucei has been established by biochemical studies demonstrating their physiological importance (6,7,13,14). However, the molecular identification of these important transporters has eluded discovery over an extended period of time.…”
Section: Trypanosoma Brucei Causes African Trypanosomiasis Inmentioning
confidence: 99%